Regulation of heme oxygenase-1 induction during recurrent insulin induced hypoglycemia - Quadri, Syed; Prathipati, Priyanka; Jackson, Debra; Jackson, Keith (International Journal of Medicine, 2014)
Background: Recurrent insulin induced hypoglycemia (RIIH) is an unavoidable risk of conventional therapeutic management of insulin dependent diabetes mellitus and is a primary cause of impaired glucose counter regulation. Circulating angiotensin II (AngII) has been reported to be elevated in diabetic models, and is linked to the promotion of hypertension. Objective: The current study was performed to evaluate the hypothesis that chronic insulin injections and/or hypoglycemia promotes hypertension via an increase in AngII, which increases endogenous carbon monoxide (CO) through an induction in heme oxygenase (HO-1). Methods: Male Sprague Dawley rats (200 – 250g) were treated for 2 weeks with daily injections of 7U/kg insulin or diluent. On the 14th day, surgery was performed and rats were administered various doses of captopril (2mg/kg, 8mg/kg, and 12mg/kg) or vehicle. Following the dose evaluation, subsets of previously treated animals were treated with vehicle, DALA (80µg/kg), Captopril (12mg/kg) or a combination of DALA (80µg/kg) + CAP (12mg/kg). Results: A dose dependent decrease in blood pressure was observed during captopril treatment in RIIH hypertensive rats. However, there was no change in urine output among the treatment groups. Captopril and DALA+CAP treatments produced a reduction in blood pressure as compared to animals treated with DALA alone. Carboxyhemoglobin and AngII concentrations were also reduced in animals treated with captopril and DALA+CAP. In addition, HO-1 protein levels in heart and kidney were reduced when compared to DALA treated animals. Conclusion: These results demonstrate that RIIH promotes an increase in circulating AngII and hypertension via an induction in HO-1, which significantly increases endogenous CO levels. Keywords: Angiotensin II, Carbon Monoxide, Heme Oxygenase, Recurring Insulin-Induced Hypoglycemia (RIIH).